2018
DOI: 10.1038/nbt.4219
|View full text |Cite
|
Sign up to set email alerts
|

Cas9-mediated allelic exchange repairs compound heterozygous recessive mutations in mice

Abstract: We report a genome-editing strategy to correct compound heterozygous mutations, a common genotype in patients with recessive genetic disorders. Adeno-associated viral vector delivery of Cas9 and guide RNA induces allelic exchange and rescues the disease phenotype in mouse models of hereditary tyrosinemia type I and mucopolysaccharidosis type I. This approach recombines non-mutated genetic information present in two heterozygous alleles into one functional allele without using donor DNA templates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…We and others recently reported that CRISPR can correct this Fah mutation through HDR [16][17][18] or allelic exchange 19 . Following correction by CRISPR, liver cells expressing the Fah enzyme, through their selective advantage, expand and repopulate the liver 14 .…”
mentioning
confidence: 94%
“…We and others recently reported that CRISPR can correct this Fah mutation through HDR [16][17][18] or allelic exchange 19 . Following correction by CRISPR, liver cells expressing the Fah enzyme, through their selective advantage, expand and repopulate the liver 14 .…”
mentioning
confidence: 94%
“…Organs traditionally known to be hard to correct, such as the heart valves and the brain, showed no improvement after therapy [85]. An additional study used CRISPR-Cas9 in vivo to target the common p.Trp402Ter mutation in a compound heterozygous mouse model of MPSI [86]. The strategy was shown to be partly efficacious in post-mitotic tissues like the heart.…”
Section: In Vivo Approachesmentioning
confidence: 99%
“…Furthermore, efforts to directly edit the genome and correct mutations are currently underway. Several groups have undertaken attempts using genome editing tools such as the CRISPR/Cas9 and ZFN systems to directly modify the endogenous Idua locus or introduce an exogenous Idua gene (Schuh et al, 2018;Wang et al, 2018;Gomez-Ospina et al, 2019). These techniques have shown preliminarily success at promoting functional IDUA and reducing GAG storage.…”
Section: Glycogen Storage Diseasementioning
confidence: 99%
“…W392X )(Wang et al, 2012) + + Crispr(Wang et al, 2018), ERT(Baldo et al, 2012) NST(Wang et al, 2012;Keeling et al, 2013) Idua (−/−)(Mendez et al, 2015) + + BT(Azario et al, 2017), HSCT(Gomez-Ospina et al, 2019) …”
mentioning
confidence: 99%